Pengaruh Pemberian Bakteri dan Trichoderma viride dari Isolat Usus Larva Black Soldier Fly (BSF) terhadap Ketahan Penyakit Cabai Keriting (Capsicum annuum) - Melanie Kristi; Yayan Sanjaya; Kusnadi Kusnadi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Capsicum annuum (curly red chili) is an important commodity for the community. The addition of chemical pesticides is used by farmers to increase plant disease resistance. The use of chemical pesticides is harmful to the environment and can have long-term effects if consumed. Therefore, biopesticide innovation is needed. Black Soldier Fly (BSF) is an insect that has bacteria and fungi in its gut. Bacteria and fungi found in BSF intestinal isolates can function as antimicrobials for plants. Because of this, in this study investigated the effect of the bacteria and fungi Trichoderma viride in increasing disease resistance in C. annuum plants. There were 4 treatments in this study, namely the administration of chemical fungicides, BSF bacterial formula, T. viride. BSF, and a mixture of bacteria and T. viride BSF. The results obtained were analyzed by calculating the Intensity of Attack (IS) score, microscopic observations in the laboratory, and statistical tests. The IS score of the control plants was 75.0%, the fungicide treatment was 37.5%, the bacterial treatment alone was 33.3%, the T. viride treatment was 19.4%, and the mixed treatment of bacteria and T. viride was 4.2%. All plants were attacked by leaf spot disease by Cercospora sp. Control plants were attacked by Sclerotium rolfsii fungus wilt and powdery mildew by Leveillula taurica and jaundice. Jaundice also attacked plants treated with T. viride only and bacteria only. The normality and homogeneity tests show that the data is not normal and not homogeneous but H1 is acceptable based on the Kruskal Wallis test. The conclusion of this study is that bacteria and T. viride from BSF are able to increase disease resistance in curly chili plants, but are not yet effective in preventing disease caused by Cercospora sp.